P52 Prisms: A Systematic Review Of The Mrc 'phase Iv' Evidence On Implementing Asthma Self-management. (10th November 2014) - Pinnock, H; Epiphaniou, E; Parke, HL; Pearce, G; Taylor, SJC
Abstract : Aim: Asthma self-management is effective in clinical trials, widely recommended by guidelines but poorly implemented. We aimed to synthesise the evidence from implementation studies of asthma self-management support interventions to inform delivery in routine clinical practice. Methods: Using systematic review methodology (Cochrane Handbook) we searched eight electronic databases, performed snowball and manual searches, and searched research databases for unpublished and on-going work. We included studies with a range of methodologies, and which evaluated the introduction of an asthma self-management support intervention in routine clinical practice. We assessed included papers for quality (Downs and Black), extracted and synthesised data on process (e.g. number of action plans issued) and clinical outcomes (e.g. measures of asthma control, unscheduled healthcare). Narrative synthesis used the whole systems approach as a framework. [PROSPERO registration: CRD42012002898]. Results: We included 18 studies (7 randomised trials, 8 longitudinal database studies, 3 uncontrolled studies) from primary, secondary, community and managed care settings in six countries. Interventions which explicitly addressed patient, professional and organisational factors (n = 7 studies) showed the most consistent improvement in both process and clinical outcomes. Targeting professionals (n = 2 studies) improved process but not clinical outcomes. Targeting patients (n = 6 studies) had inconsistent impact on process/clinical outcomes. Targeting the organisation (n = 3 studies) improved process, and had a small effect on clinical outcomes. Authors highlighted the importance of a healthcare system committed to supporting self-management, skills training for professionals, patient education programmes supported by regular reviews, and on-going evaluation of the implementation process. Conclusion: Effective interventions were complex: actively engaging patients, and training and motivating professionals within the context of an organisation which prioritised supported self-management. Commissioners and providers of services for people with asthma should consider how they can promote a culture of supporting self-management as a normal, expected, monitored and remunerated aspect of the provision of care. Funding: NIHR HS&DR programme (project number 11/1014/04). The views and opinions expressed therein are those of the authors and do not necessarily reflect those of the Hs and DR programme, NIHR, NHS or the Department of Health.